A Literature Review on the Interactions Between Climate Change and Tuberculosis: Impacts on Epidemiology, Transmission, and Control - Tan, Suriyani; Suyanto, Jipri; Panjaitan, Novaria Sari Dewi; Hidayat, Syarif; Fitriana, Fitriana; Sunarno, Sunarno; Lienggonegoro, Lisa Andriani (Universitas Aisyah Pringsewu, 2024)
Climate change is increasingly recognized as a contributor to public health challenges, including the spread of infectious diseases such as tuberculosis (TB). Environmental changes, such as rising temperatures, altered precipitation patterns, and extreme weather events, can directly and indirectly influence TB transmission dynamics. Additionally, climate change exacerbates socio-economic issues like poverty, food insecurity, and displacement, further increasing vulnerability to TB. Understanding the complex relationship between climate change and TB is crucial for developing effective prevention and control strategies. This literature review explores the relationship between climate change and TB, focusing on the impact of climatic factors on TB epidemiology, transmission, and control measures. A systematic evaluation of peer-reviewed studies was conducted using databases such as Science Direct, PubMed, DOAJ, and Google Scholar. Research on climatic factors (e.g., temperature, humidity, extreme weather events) and their effects on TB transmission, as well as the socio-economic consequences of climate change, was analyzed. The PICOS framework and PRISMA guidelines were applied to ensure a comprehensive review. The findings reveal that elevated temperatures and humidity can enhance the survival and spread of Mycobacterium tuberculosis, potentially increasing TB transmission rates. Extreme weather events, such as floods and droughts, disrupt healthcare services and create overcrowded living conditions, fostering TB outbreaks. Socio-economic factors, including poverty, starvation, and migration, further heighten TB risks. Climate change-induced disruptions to health infrastructure, particularly in low- and middle-income countries, hinder TB diagnosis, treatment, and control efforts. However, there is a lack of long-term studies assessing the cumulative effects of climate change on TB. This review highlights the urgent need for interdisciplinary approaches to address the dual challenges of climate change and TB. Effective TB control programs must integrate climate adaptation and resilience strategies. Policymakers should prioritize climate-informed TB initiatives, enhance monitoring systems, and support further research to address gaps in understanding the long-term impacts of climate change on TB.